Shout praises! kids gospel the ultimate praise party - Moen, Don.; Thomason, Chris; Moore, Ric.; MMGSL (Firm); Integrity Media (Firm); Sony Music Entertainment, Inc. (Mobile, AL : Integrity Media : Distributed by Sony Music Entertainment, 2003)
Nine original music videos of children singing gospel songs. Includes exciting graphics and on-screen lyrics to make viewers shout, dance, and praise.
When the spirit of the Lord -- You are good -- Lord, I lift your name on high -- I will praise -- Jubilee -- In the sanctuary -- Who is like the Lord -- Wanna praise you -- He knows my name.
Title from container.
Photography, Ric Moore.
MPAA rating: Not rated.
DVD.
Closed-captioned.
Keywords: Praise of God -- Juvenile films; Contemporary Christian music; Children's films; Music videos; Video recordings for the hearing impaired